Bank Debt and Corporate Governance - Ivashina, Victoria; Nair, Vinay B.; Saunders, Anthony; Massoud, Nadia; Stover, Roger (Review of Financial Studies, 2009)
In this paper, we investigate the disciplining role of banks and bank debt in the market for corporate control. We find that relationship bank lending intensity and bank client network have positive effects on the probability of a borrowing firm becoming a target. This effect is enhanced in cases where the target and acquirer have a relationship with the same bank. Moreover, we utilize an experiment to show that the effects of relationship bank lending intensity on takeover probability are not driven by endogeneity. Finally, we also investigate reasons motivating a bank's informational role in the market for corporate control.